1999
DOI: 10.1080/02688699943150
|View full text |Cite
|
Sign up to set email alerts
|

Rapid spontaneous resolution of an acute extradural haematoma: case report

Abstract: A case of acute extradural haematoma with spontaneous resolution within 6 h of the head injury is presented. The literature is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 12 publications
1
19
0
1
Order By: Relevance
“…Fifteen cases have been reported in the literature with a resolution less than 24 hours, including our case; these are summarized in Table 1 (2)(3)(4)(5)(6)(7)(8)(9). Of the patients, ten were pediatric (under age 18) and five were adults.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Fifteen cases have been reported in the literature with a resolution less than 24 hours, including our case; these are summarized in Table 1 (2)(3)(4)(5)(6)(7)(8)(9). Of the patients, ten were pediatric (under age 18) and five were adults.…”
Section: Discussionmentioning
confidence: 92%
“…Aoki et al (2) reported that skull fracture has a positive impact on prognosis as it provides a connection between the epicranial and epidural spaces. Two EDH cases with fractures including the external auditory canal have been published in the literature and rapid spontaneous resolution without an increase in intracranial pressure was reported (5,8). However, Gülşen et al (9) reported a 4 year-old with a case of spontaneous resolution without skull fracture.…”
Section: Discussionmentioning
confidence: 99%
“…The angioblasts form sinusoids that gradually connect with the marginal dural vessels, so blood and blood products can return to the systemic circulation via the permeable membrane of these sinusoids. [1,5,6,[11][12][13] However, such hematoma resolution is reported as longer than three weeks. [6][7][8] Medical treatment, repeated CT scan and close neurological follow-up are essential in the conservative management.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,4,[6][7][8]10,11) The hematoma may be forced out of the intracranial region by the high intracranial pressure associated with severe cerebral edema. 6,10) In such patients, outcomes would be poor.…”
Section: Discussionmentioning
confidence: 99%
“…5) Spontaneous rapid (within 24 hours) resolution of EDH via a skull fracture has also been reported in several age groups other than infants. 1,3,4,[6][7][8]10,11) We report the case of an infant showing spontaneous slow drainage of EDH into the subgaleal space through a skull fracture.…”
Section: Introductionmentioning
confidence: 99%